Verlustfreie Übersetzungen - Walter Schilling (Recherches Germaniques)
This article deals with Eugen Gomringer’s ideograms and their translations. It points out that there is no loss of meaning in the different versions in German, French, English, and Spanish. That Gomringer succeeds in this is examined primarily through Gomringer’s medial games between white space, black letters, orality, and writing. An attempt is made to establish that Gomringer’s linguistic reduction offers the prospect of a form of transnational communication in which it is not necessary to master all the prevailing linguistic norms. Instead, it is for the audience to fill in the empty space themselves, and to discover silence and secrecy there.